2022
DOI: 10.1186/s10020-022-00493-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine induces apoptosis of myeloid-derived suppressor cells via up-regulation of CD81 contributing to alleviate lupus symptoms

Abstract: Background Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder that results from widespread immune complex deposition and secondary tissue injury. Hydroxychloroquine (HCQ) has been used clinically to treat SLE, while its exact mechanism has still remained elusive. Some studies have shown that myeloid-derived suppressor cells (MDSCs) play a vital role in the regulation of SLE. In this study, we aimed to explore the effects of HCQ on the apoptosis of MDSCs in lupus mice and its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(71 reference statements)
3
3
0
Order By: Relevance
“…28 Notably, dysregulation of Th17 cells and Treg cells with an increase in Th17 cell populations and a decrease in Treg cell populations has been observed in systemic lupus erythematosus. 29 Our study aligns with these observations, as we identified an elevated proportion of Th17 cells and a reduced proportion of Treg cells in CSU patients. IL-22 and IL-17 are crucial cytokines involved in the immune defense of psoriatic plaques through their ability to facilitate the production of antimicrobial proteins.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…28 Notably, dysregulation of Th17 cells and Treg cells with an increase in Th17 cell populations and a decrease in Treg cell populations has been observed in systemic lupus erythematosus. 29 Our study aligns with these observations, as we identified an elevated proportion of Th17 cells and a reduced proportion of Treg cells in CSU patients. IL-22 and IL-17 are crucial cytokines involved in the immune defense of psoriatic plaques through their ability to facilitate the production of antimicrobial proteins.…”
Section: Discussionsupporting
confidence: 91%
“… 28 Notably, dysregulation of Th17 cells and Treg cells with an increase in Th17 cell populations and a decrease in Treg cell populations has been observed in systemic lupus erythematosus. 29 Our study aligns with these observations, as we identified an elevated proportion of Th17 cells and a reduced proportion of Treg cells in CSU patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These data indicated that PDAC patients had a higher expression of S100A family members, which was found to be associated with tumor aggressive and metastasis previously ( 28 ). Up-regulation of S100A9 expression inhibited the differentiation of DCs and macrophages and induced accumulation of MDSCs ( 29 ). We found that the proportion of S100A9 + monocytes was significantly up-regulated in PDAC patients compared to the healthy controls ( Figures 6F, G ).…”
Section: Resultsmentioning
confidence: 99%
“…In patients with SLE, the accumulation of myeloid-derived suppressor cells (MDSCs) is positively correlated to disease activity. Hydroxychloroquine may relieve the symptoms of SLE inflammation by regulating the expression of CD81 in MDSCs and inducing their apoptosis ( Ni et al, 2022 ). Taken together, promoting the apoptosis of key cells in inflammatory diseases and reducing the secretion of inflammatory cytokines are crucial in alleviating inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%